2014
DOI: 10.1188/14.onf.130-140
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Ethical Conflicts and the Meaning of Moral Community in Oncology Practice

Abstract: Practice environments as moral communities could foster comfortable dialogue about moral differences and prevent or mitigate ethical conflicts and the moral distress that frequently follows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 53 publications
0
46
0
1
Order By: Relevance
“…1,2,5,[8][9][10][11][12] Leuter and colleagues 11 found that most nurses experienced recurrent ethical problems and did not feel effectively supported by the health care system. These include futile or nonbeneficial care, pain management, patient autonomy (lack of decisional capacity, patient confidentiality or privacy), advance care planning (disregard of patients' wishes), communication difficulties, conflicts between patients/families and health providers, and conflicts between nurses and colleagues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,5,[8][9][10][11][12] Leuter and colleagues 11 found that most nurses experienced recurrent ethical problems and did not feel effectively supported by the health care system. These include futile or nonbeneficial care, pain management, patient autonomy (lack of decisional capacity, patient confidentiality or privacy), advance care planning (disregard of patients' wishes), communication difficulties, conflicts between patients/families and health providers, and conflicts between nurses and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 60% of ethical dilemmas were associated with truth telling. 1,5,9,11,12,16 Futile treatments may lead to increased pain, loss of dignity, and patient's decreased quality of life. Barriers to truth telling included physicians' avoidance of discussing ethical issues, fear of destroying a patient's hope, and patient's lack of decisional capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In addition, they described nine types of ethically difficult situations: end-of-life situations with futility as a major concern; end-of-life situations with patient autonomy as a primary issue; fidelity to RN obligations but medical team not listening; end-of-life situation with honesty about prognosis a concern; patient capacity to provide informed consent for clinical trial; pain management when drug-seeking behavior is suspected; adolescent patients with cancer above age 18 years but parents continue to make all decisions; mental health capacity to comply with complex treatments; justice issues with insurance company refusal to cover treatment. 10,11 …”
Section: Ethics At the Bedsidementioning
confidence: 98%
“…This obligation to the patient comes into play in the following situations: the patient and family disagree on the goals of care; the family and patient disagree on code status; the family attempts to override the patient's advance directives; the family attempts to interfere with symptom management, especially around the use of opioids; the family does not want the patient to know their diagnosis (''don't tell mama''); or the family's voice drowns out that of the patient, who's voice is lost. [9][10][11] The importance of nurses' moral sensitivity and advocacy in recognizing and addressing these issues is clear. 12,13 CASE The patient is a 76-year-old man who was diagnosed at a community hospital with neuroendocrine cancer with metastases to the liver.…”
Section: Ethics At the Bedsidementioning
confidence: 99%